Student’s Perspective and Teachers’ Metacognition: Applications of Eye-Tracking in Education and Scientific Research in Schools - da Silva Soares, Raimundo; Lukasova, Katerina; Carthery-Goulart, Maria Teresa; Sato, João Ricardo (Frontiers in Psychology, 2021)
This Perspective article discusses the possible contributions of eye-tracking (ET) to the field of Educational Neuroscience based on an application of this tool at schools. We sought to explore the teachers' view of ET videos recorded while students solved mathematical problems. More than 90% of the teachers could predict with great accuracy whether the students had answered the questions correctly or not based solely on the information provided by the ET videos. Almost all participants tried to translate the students' thoughts to understand the strategy used by the children. Our results highlight the relevance of qualitative analysis to identify the gaze strategies used by students. We propose that ET allows teachers to gain critical feedback about students' behavior during problem-solving. Most previous studies tend to emphasize the benefits of eye-tracking applications to explore learners' cognition. Our findings point that this system can also be useful to investigate teachers' cognition by providing metacognitive experiences.